MEMBANGUN KOMUNITAS AGAMA MELALUI PLATFORM DIGITAL: ANALISIS FORUM ONLINE - Gerbin Tamba (Journal of Digital Informatics, 2025)
This study aims to explore the role of digital platforms, particularly online forums, in building and strengthening religious communities. With the increasing use of technology within the Church and society, it is crucial to understand how online interactions can impact religious practices and solidarity among community members. Through this study, we analyze the benefits and challenges faced by religious communities in using digital platforms.